2020
DOI: 10.1111/ajd.13401
|View full text |Cite
|
Sign up to set email alerts
|

Rosacea and the gastrointestinal system

Abstract: Rosacea is a common skin condition characterised by erythema, papules and pustules. Increasing evidence suggests that the gut-skin axis is implicated in the pathogenesis of rosacea. Sufficient evidence exists to support the notion that the gut microbiome plays a role in the inflammatory cutaneous response and there appear to be associations with small intestinal bacterial overgrowth and Helicobacter pylori infection. A dysbiotic microbiome and an innate immune system dysregulation contribute to the pathophysio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 34 publications
0
22
0
3
Order By: Relevance
“…The cytokines observed (including interleukin-8 (IL-8) and tumor necrosis factor alpha (TNFa)) promote angiogenesis, highlighting a potential cause of the long-standing, prominent telangiectasias often present in rosacea. It has been suggested that D. folliculorum's exoskeleton itself incites the production of inflammatory markers [13].…”
Section: Demodex Folliculorummentioning
confidence: 99%
See 4 more Smart Citations
“…The cytokines observed (including interleukin-8 (IL-8) and tumor necrosis factor alpha (TNFa)) promote angiogenesis, highlighting a potential cause of the long-standing, prominent telangiectasias often present in rosacea. It has been suggested that D. folliculorum's exoskeleton itself incites the production of inflammatory markers [13].…”
Section: Demodex Folliculorummentioning
confidence: 99%
“…In an additional layer of complexity, B. oleronius, a gram-negative Demodex-associated bacteria, triggers inflammatory pathways in its own right [7,8,13]. This microorganism has been demonstrated to produce antigenic proteins that potentially play a role in PPR, ETR, and ocular rosacea [8].…”
Section: Bacillus Oleroniusmentioning
confidence: 99%
See 3 more Smart Citations